Buerger Allen Exercise terhadap Sirkulasi dan Sensori Perifer pada Pasien dengan Diabetes Melitus - Fina Mahardini; Debie Dahlia; Dikha Ayu Kurnia; Etty Rekawati (Jurnal Keperawatan Silampari, 2023)
This study aims to systematically evaluate the results of studies assessing the effectiveness of the Buerger Allen Exercise (BAE) in improving circulation and peripheral sensory status in patients with Diabetes Mellitus (DM). The method used is a systematic review in which researchers carry out a comprehensive and systematic search based on PRISMA's recommendations for research articles using randomized controlled trial (RCT) methods, quasi-experiments, and cohorts using the keywords "diabetes," "Buerger Allen, "perfusion," "neuropathy," and related MeSH terms published in international journals over the last five years. The results showed that of the nine articles included, six proved the effectiveness of BAE in improving peripheral circulation, two reports showed their effectiveness in improving peripheral neurosensory, and one other showed the efficacy of BAE in improving peripheral circulation and neurosensory. In conclusion, BAE can significantly improve DM patients' circulation and peripheral sensory status. Keywords: Buerger Allen Exercise (BAE), Diabetes Mellitus, Peripheral Sensory, Peripheral Circulation